Point-of-care HIV viral load and targeted drug resistance mutation testing versus standard care for Kenyan children on antiretroviral therapy (Opt4Kids): an open-label, randomised controlled trial. (October 2022) - Patel, Rena C; Oyaro, Patrick; Thomas, Katherine K; Wagude, James; Mukui, Irene; Brown, Evelyn; Hassan, Shukri A; Kinywa, Eunice; Oluoch, Frederick; Odhiambo, Francesca; Oyaro, Boaz; Kingwara, Leonard; et al.
Summary: Background: Feasible, scalable, and cost-effective approaches to ensure virological suppression among children living with HIV are urgently needed. The aim of the Opt4Kids study was to determine the effect of point of care viral load and targeted drug resistance mutation testing in improving virological suppression among children on antiretroviral therapy (ART) in Kenya. Methods: In this open-label, individually randomised controlled trial, we enrolled children living with HIV aged 1–14 years and who were either newly initiating or already receiving ART at five study facilities in Kenya. Participants were randomly allocated 1:1 to receive the intervention of point-of-care viral load testing every 3 months, targeted drug resistance mutation testing, and clinical decision support (point-of-care testing) or to receive the standard care (control group), stratified by facility site and age groups (1–9 years vs 10–14 years). Investigators were masked to the randomised group. The primary efficacy outcome was virological suppression (defined as a viral load of <1000 copies per mL) by point-of-care viral load testing at 12 months after enrolment in all participants with an assessment. This study is registered with ClinicalTrials.gov, NCT03820323. Findings: Between March 7, 2019, and December 31, 2020, we enrolled 704 participants. Median age at enrolment was 9 years (IQR 7–12), 344 (49%) participants were female and 360 (51%) were male, and median time on ART was 5·8 years (IQR 3·1–8·6). 536 (76%) of 704 had documented virological suppression at enrolment. At 12 months after enrolment, the proportion of participants achieving virological suppression in the intervention group (283 [90%] of 313 participants with a 12 month point-of-care viral load test) did not differ from that in the control group (289 [92%] of 315; risk ratio [RR] 0·99, 95% CI 0·94–1·03; p=0·55). We identified 138 episodes of viraemia in intervention participants, of which 107 (89%) samples successfully underwent drug resistance mutation testing and 91 (85%) had major drug resistance mutations. The median turnaround time for viral load results was 1 day (IQR 0–1) in the intervention group and 15 days (10–21) in the control group. Interpretation: Point-of-care viral load testing decreased turnaround time and targeted drug resistance mutation testing identified a high prevalence of HIV drug resistance mutations in children living with HIV, but the combined approach did not increase rates of virological suppression. Further research in combination interventions, including point-of-care viral load and drug resistance mutation testing coupled with psychosocial support, is needed to optimise virological suppression for children living with HIV. Funding: National Institutes of Mental Health of the US National Institutes of Health, Thrasher Research Fund.